2018
DOI: 10.1007/s11367-018-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a product sustainability budget at an automotive company—one option to increase the use of LCSA results in decision-making processes

Abstract: Purpose:The assessment and improvement of sustainability impacts of products is integral to achieve sustainable development. A way to assess the impact of a product over its entire life cycle on all three dimensions of sustainability (environment, economy and society) is Life Cycle Sustainability Assessment (LCSA). LCSA suggests to carry out three complementary assessments: Life Cycle Assessment (LCA), Life Cycle Costing (LCC) and Social Life Cycle Assessment (S-LCA). While LCA is widely applied across various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 215 publications
(288 reference statements)
0
3
0
Order By: Relevance
“…Tarne, et al [246] have introduced the concept of a "product sustainability budget" which can be used alongside the LCSA evaluation as a decision support tool. Using the example of an automotive manufacturer selling various models of car, they suggest that certain customers may be willing to pay a premium for a car with a 'sustainability interior package'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarne, et al [246] have introduced the concept of a "product sustainability budget" which can be used alongside the LCSA evaluation as a decision support tool. Using the example of an automotive manufacturer selling various models of car, they suggest that certain customers may be willing to pay a premium for a car with a 'sustainability interior package'.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the profits from this sustainability interior package would be reinvested in a product sustainability budget out of which sustainability improvements across the range of vehicles would be financed. Since these improvements are already accounted for in this budget, their additional cost does not adversely affect the overall LCC performance [246]. Crucially, this "product sustainability budget" acts as an interface with the LCSA evaluation, helping managers to identify sustainability improvements from the LCSA, which lead to the largest improvement in sustainability performance without negatively impacting the LCC performance.…”
Section: Methodsmentioning
confidence: 99%
“…There is often lack of data, uncertainty in what data to use, or low levels of data quality (de Oliveira et al, 2015; "We can never be really sure of the data" Interpretation and communication (5) Some properties or indicators may be hard to communicate (Bertoni et al, 2020) and might be unfamiliar to decision makers (Tarne et al, 2019).…”
Section: "It Might Actually Be Helpful As It Prompts You To Better Un...mentioning
confidence: 99%
“…After the elimination of duplicates, 13 publications remained, which indicated single terms or combinations of the mentioned search terms in the title, abstract or in key words. After a detailed examination of the content, we found that a majority of the publications used their surveys to: obtain primary data especially for LCA [11][12][13], to understand and set up relevance and ranking of indicators, e.g., midpoint indicators in LCA [14][15][16], to explicitly implement a Social Life Cycle Assessment [11,17], or to make decisions in the automotive sector regarding sustainability assessment indicators [18,19].…”
Section: Theoretical Background 21 State-of-the-artmentioning
confidence: 99%
“…Further focusing on correlations from educational background, working sector and age; the equivalent execution of the three pillars seems to be more challenging for the consulting sector and for younger (18-29 years) and older experts (>60) than for the average respondent; data availability is named by almost all experts as partly challenging, except for those working in industry (more challenging); in particular, data availability in S-LCA seems to be more challenging for industry and consulting than for university staff or employees of research institutes; defining equivalent system boundaries is more challenging for younger (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and older (>60) age groups; and in the interpretation and presentation of the results of LCSA, the consulting sector mentioned increased challenges.…”
Section: Challenges (Question 12-20)mentioning
confidence: 99%